THE OBJECTIVE NECESSITY AND SOCIO-ECONOMIC IMPORTANCE OF INCREASING LABOR EFFICIENCY IN ENTERPRISES - Ganiev Baydulla Tashmurodovich (Galaxy International Interdisciplinary Research Journal, 2023)
It is proposed to ensure the sustainable development of enterprises, reduce labor costs for production, and improve labor quality and labor efficiency.